Transient infantile hypertriglyceridemia caused by GPD1 deficiency report of two cases and literature review - Xie, X B (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2020)
Objective: To investigate the clinical phenotype and genotype of transient infantile hypertriglyceridemia (HTGTI). Methods: The clinical data of two HTGTI children, diagnosed at Children's Hospital of Fudan University from July 2019 to January 2020, were collected and analyzed retrospectively. The literature up to 25th January 2020 were searched in PubMed, CNKI and Wanfang databases with the key words of "hypertriglyceridemia" and "glycerol phosphate dehydrogenase-1 (GPD1)". Results: Two children, including a 5-month-old female and a 13-month-old male, who presented with hepatomegaly, hypertriglyceridemia, transaminase elevation and hepatic steatosis, were admitted to the hospital. Gene detection found compound heterozygous variation of GPD1. After a low-fat diet with enriched medium-chain fatty acids, their plasma triglyceride level were significantly decreased, and finally normalized in case 2. Literature review found 17 patients with GPD1 gene variation reported in 5 papers, including 16 HTGTI cases and one case of different phenotype. Most of the cases presented with hepatomegaly, hypertriglyceridemia and transaminase elevation, while some had developmental retardation, splenomegaly, hypoglycemia, obesity and insulin resistance. The c.361-1G>C was the most common variation of GPD1. Conclusions: HTGTI caused by GPD1 deficiency is mainly manifested with hepatomegaly, hypertriglyceridemia, transaminase elevation as well as hepatic steatosis and fibrosis. The most common variation of GPD1 is c.361-1G>C